Institutional and technical drivers of intra-household marketing decisions for smallholder farmers in Uganda: evidence from Northern Uganda - Lukwago, Moses Mwesige; Micheal Okello, Daniel; Mugonola, Basil (Taylor & Francis Ltd, 2025)
Agricultural output marketing as an economic venture, increases smallholders’ economic welfare (incomes) through market participation. However, the venture is plagued by inefficiencies that emanate from incomplete institutional and physical infrastructures as well as imperfect competition. Data were obtained from a random sample of 206 farmers in Nwoya district. A Tobit regression was conducted to determine the institutional (and technical) drivers of farmers’ intra-household market participation decisions. The results revealed that variety used (p < 0.1), group membership (p < 0.01), markets (p < 0.05), road access (0.05), distance to markets (p < 0.05), total labor (p < 0.05) and household size (p < 0.1) significantly influenced intra-household market participation decisions. The outcome of this study provides a course-way upon which government institutions and relevant stakeholders can make strides through addressing policies aimed at enhancing sustainable economic welfare through increased productivity which reduces poverty and boosts food security among famers.